MASTALGIA - Kartikaputri, Dwi Andhayani; Widiana, Ketut (E-Jurnal Medika Udayana; vol 3 no 3 (2014):e-jurnal medika udayana, 2014)
Mastalgia is painful symptoms in the absence of abnormalities in the breast physiology and pathology of the breast parenchyma. More than 80% of all cases mastalgia is a mild case. The exact causes of mastalgia has not yet been sufficiently studied, but few studies relate endocrine abnormalities, inflammation, pcyconeurosis, improper nutrition, and consumption of certain drugs. Based on the occurrence, mastalgia divided into two categories, namely mastalgia cyclic (related to the endocrine system) and mastalgia noncyclic (associated with the nonendokrin system). Noncyclic mastalgia conditions can be divided into two categories, which comes from the breast (true noncyclic breast pain) and in addition breasts (extramammary pain). Each classification of mastalgia had typical clinical picture, so the majority mastalgia diagnosis can already be diagnosed through a complete clinical examination. The most important of mastalgia management is reassurance. This method will greatly affect the psychology of patients and are associated with the severity of symptoms and response to therapy received by patients. 1 Non-pharmacological and pharmacological therapies may be done in accordance with the indications. Surgical treatment is not recommended unless there is a definite indication.
Keywords: mastalgia, clinical examination, reassurance